HAMBATAN PENGGUNAAN KOMPUTER SEBAGAI MEDIA (E-LEARNING) DI SMP NEGERI 4 LIMBOTO - Ricky Daliuwa; Herman Didipu (Jambura Journal of Linguistics and Literature, 2022)
The purpose of writing this article is to describe the obstacles to using electronic devices, namely computers, which are e-learning media at Limboto 4 Public Middle School, Gorontalo Regency, Gorontalo Province. Data collection techniques used in this article are documentation and interview techniques. The data obtained is actual data that has undergone an interview process from several sources. The results of this article indicate that SMP Negeri 4 Limboto has obstacles in using computers as e-learning media, namely the lack of several technological tools such as internet computers in the library room, limited projector facilities to facilitate or support the learning process in class, as well as a lack of facilitators. who are experts in the application of materials and practices in the use of information technology.